Saturday

August 23, 2014

August 23, 2014

Posted by **Anonymous** on Saturday, January 31, 2009 at 8:29pm.

f(x)-x^2-1 what is the equation for f^-1(x)?

f(x)=3x+2, find f(f^-1(14)).

f(x)=4x+7 and g(x)=3x-5 find (f*g)(-4)

f(x)=sqrt x+3 what is equation for f^-1(x)?

Graph y=sqrt x-2 +5 which point lies on graph?

A(7,6) B(0,5) C(-2,5) D(3,6)

The graph y=sqrt x is shifted 6 points down and 1 unit right. Which equation represents the new graph.

y=sqrt x+1 -6

y=sqrt x-6 +1

y= sqrt x-1 -6

y= sqrt x+6-1

any help would be appreciated.

- math-Inverse functions -
**drwls**, Sunday, February 1, 2009 at 1:03amI am not going to do all of these but will show you how to do one.

Your question is

f(x) = x^2-1

what is the equation for f^-1(x)?

f^-1(x) is called the inverse function of f(x). It is the function which gives you back "x" when you apply it to f(x)

Let's call f(x) just y, to make the notation look easier.

y = x^2 -1

Solve for x

x= sqrt (y+1)

Now switch the variables

y = sqrt (x+1)

That is the inverse function of f(x). That's all there is to it!

Proof: If I take sqrt(x+1), square it, and subtract 1, what do I end up with? x. Therefore applying f(x) to f^-1(x) gives me back x.

**Related Questions**

Calculus - Find the sum and difference functions f + g and f – g for the ...

inverse - find f^-1 (x). (this is asking me to find the inverse) f(x) = -(x-2)^2...

college algebra - For the given functions f and g find the following and state ...

algebra - 1 (a) A function passes through the points (0, -5), (1, 0), (2, 7). ...

math - consider the functions f(x)=x^3-2 and g(x)=3 sqrt x+2: a. find f(g(x)) b...

math - for the given functions f and g find f o g and state the domain show all ...

Algebra 2 - Operations with Complex Numbers Simplify. 1. sqrt(-144) 2. sqrt(-64x...

pre-cal - for the given functions f & g find the specified value of the ...

Calculus - Math questions, please help me? :(? Find the composite functions f o ...

Math - How do i find the domain and range of these functions? f(x)=x+1 f(x)=2/x ...